2014
DOI: 10.3390/ijms150813236
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Phosphoinositide-Specific Phospholipases Cγ1 Contributes to Extracellular Matrix Synthesis of Human Osteoarthritis Chondrocytes

Abstract: Osteoarthritis (OA) is a degenerative joint disease characterized by articular cartilage degradation including extracellular matrix (ECM) degradation and cell loss. It is known that phosphoinositide-specific phospholipase γ1 (PLCγ1) can trigger several signaling pathways to regulate cell metabolism. However, whether this kinase is expressive and active in human OA chondrocytes and its role in the pathological progression of OA have not been investigated. The current study was designed to investigate the PLCγ1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 26 publications
2
25
0
Order By: Relevance
“…The incidence of OA increases with age, and thus becomes a major problem in ageing populations [3]. For decades, OA has been regarded as a pathological condition resulting from the degeneration or destruction of the articular cartilage tissue, in which the extracellular matrix (ECM) served as primary target of articular cartilage [4]. However, this view ignored the involvement of articular chondrocytes, as potential instigator of OA.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of OA increases with age, and thus becomes a major problem in ageing populations [3]. For decades, OA has been regarded as a pathological condition resulting from the degeneration or destruction of the articular cartilage tissue, in which the extracellular matrix (ECM) served as primary target of articular cartilage [4]. However, this view ignored the involvement of articular chondrocytes, as potential instigator of OA.…”
Section: Introductionmentioning
confidence: 99%
“…Our results show that Phlpp1 is a regulator of endochondral bone development, as chondrocyte proliferation and matrix synthesis are enhanced in Phlpp1-deficient mice. This likely occurs due to the ability of Phlpp1 to directly control the activity of anabolic signaling pathways, including Akt2, PKC, and p70 S6 kinase, that are known facilitators of proliferation and matrix production by chondrocytes (21,37,38). Activation of these pathways triggers subsequent events, including but not limited to, Fgf18 production and downstream activation of Fgfr and Mek/Erk signaling.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the association between Ras-GRF1/2 and PLCγ1 is required for Ras signaling, ERK activation and MMP-3 release downstream of IL-1 stimulation in NIH 3T3 fibroblasts, showing the crosstalk between ERK and PLCγ1 [ 13 ]. Therefore, it is confirmed that the interplays of PLCγ and mTOR or PLCγ and ERK are involved in cell metabolism in some cell types [ 8 , 12 , 13 ]. Otherwise, the crosstalk of PLCγ1, mTOR, and ERK in OA pathogenesis is not elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, phosphoinositide-specific phospholipases γ (PLCγ), as one of the phosphoinositide-specific phospholipases families [ 9 , 10 ], has recently been shown to be involved in the sex-specific response of rat costochondral cartilage growth plate chondrocytes to 17β-estradiol [ 11 ]. Especially, our previous study showed that PLCγ1 has higher expression and promotes matrix degradation by triggering the mTOR pathway in human OA chondrocytes [ 12 ]. These studies display the involvement of PLCγ1 in chondrocyte metabolism and the existence of PLCγ1/mTOR axis.…”
Section: Introductionmentioning
confidence: 99%